”Åh vad kul, nu börjar det invandrare på skolan!” - Fanny Pérez-Aronsson (Educare)
This article criticizes the idea of schools as institutions of anti-racist knowledge and values, as well as schools as institutions of equal opportunity for all students, by examining how youths retell experiences of racism within the Swedish education system in online discussion fora. The study focuses on youths’ experiences of racism in meetings with teachers, in particular, as teachers are positioned as representatives of schools and often regarded as carriers of anti-racist knowledge and values to be taught to their pupils. Using a phenomenological approach, the study focuses how pupils attempt to reproduce institutional life lines promoting school success and upwards social mobility and how such attempts are interrupted by teachers, all the while forcing the pupils to embody a “happy diversity”. The article uses netnographic data from two online forums for racialized youth to highlight their experiences as shared online in a “safe space”, created specifically for them, and how such spaces constitute an alternative educational space beyond the limitations and regulations of their everyday school environments.